The practice and effectiveness of distributed leadership among principals in selected islamic private secondary schools in Narathiwat, Thailand : teachers' perception - Thepluksana, Hamran (Institute of Education, International Islamic University Malaysia, 2013)
This study examined the practice and effectiveness of distributed leadership among principals in Islamic private secondary schools in Narathiwat, Thailand. An attempt was also made to explore teachers' perception of the practice and effectiveness of distributed leadership among principals in Narathiwat. To achieve these purposes, a questionnaire was specifically designed to get information from the respondents who were teachers. The descriptive analysis method was employed to describe the teachers' perception regarding practice and effectiveness of distributed leadership. A questionnaire, using Five Point Likert Scale, was used as the instrument to collect the data. The sample of this study was randomly selected. A total of 302 respondents from 10 schools, consisting of 94 male and 208 female teachers were selected for this study. Percentages, means, standard deviations, t-test and Anova were computed for research questions. The analysis revealed that the teachers' perception towards principals' practice and effectiveness of distributed leadership in Islamic private secondary schools in Narathiwat generally appear to be positive. The findings also indicated that the teachers' perception showed a non-statistical significant difference based on gender, qualification and years of teaching experience. However, the finding showed a statistical relationship between the principals' practice and effectiveness. Finally, the study provided recommendations on how to improve the practice of distributed leadership practice in schools and suggested interesting further researches.